Non-single bionic coupling model for thermal fatigue and wear resistance of gray cast iron drum brake. (April 2019) - Yu, Dahui; Zhou, Ti; Zhou, Hong; Bo, Haifeng; Lu, Haiqiu
Highlights: The single 0° stripe model yielded the best thermal fatigue resistance. The single 45° mesh model yielded the highest friction coefficient. The non-single bionic coupling mesh model has the optimal effect on the drum brake. The laser processing parameters for specimens and drum brakes are different. A bionic coupling drum brake's service life is twice longer than a common drum brake. Abstract: Laser bionic coupling treatment technology can improve the thermal fatigue and wear resistance of gray cast iron. In this study, many single bionic coupling models were designed to determine the thermal fatigue and friction coefficients, and the single model yielding the best thermal fatigue resistance and optimal wear resistance was identified. Crack development and growth on the inner wall of the drum brake were investigated and, based on the results, a non-single bionic coupling model was proposed. The wall thickness of the drum brake was significantly higher than that of the thermal fatigue specimen. According to the Bessel function, to obtain the same unit bodies, the laser energy required for the brake should be greater than that required for the thermal fatigue test specimen. Therefore, an orthogonal test was used to obtain the bionic coupling unit body suitable for the drum brake and, based on the results, a bionic coupling drum brake was manufactured. This brake and an unprocessed drum brake (as a control) were subjected to a bench test. The results revealed that, under the same conditions, specimens with the non-single mesh model exhibited better thermal fatigue and wear resistance than the unprocessed brake. Similarly, the service life of the bionic coupling brake was at least twice that of the unprocessed brake.